A noise-filtering event generator for PIDPlus controllers. Issue 2 (January 2018) - Merigo, Luca; Beschi, Manuel; Padula, Fabrizio; Visioli, Antonio
Abstract: In this paper we propose a new event generator, which has strong noise-filtering capabilities, to be used in event-based control systems with a PIDPlus controller. An approximate frequency analysis is performed in order to characterize the event generator system and tuning guidelines are provided for its design parameter. Simulation and experimental results obtained with a laboratory setup demonstrate the effectiveness of the methodology in providing a satisfactory performance related to set-point and load disturbance step responses with a total variation that is significantly reduced with respect to the standard cases.